Learning from Mistakes: The Implications of Course Repetition for Student Subsequent Success - Kelly Chen; Xuan Jiang (Institute of Labor Economics (IZA), 2023)
Most colleges allow low-performing students to make a repeated attempt for the same course, but little is known about its implications for the academic success of these students. Using the variations in repetition induced by the cancellation and reversal of a university GPA policy to correct for student selection, we quantify the effects of course repetition on below-average students' subsequent outcomes. We find that students develop greater interest, persist longer, and perform better in a given subject upon repetition in comparison to their non-repeating classmates who receive the same initial-attempt grade. The observed repetition effects are particularly pronounced for the students who are exposed to the college environment and/or a subject matter for the first time and are entirely explained by the gains in learning. Importantly, while boosting graduation rates, a moderate number of repetitions during a student's undergraduate career is not found to cause any disruptions to the student's routine progress in pursuing a degree.
Keywords: I23; I24; J24; 330; course repetition; grade replacement; college student success; graduation; time-to-degree